Monopsony competition and the minimum wage: Evidence from Germany - Ronald Bachmann; Hanna Frings (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper investigates the degree of monoposony power of German employers in different industries, using a semi-structural approach based on a dynamic model of monopsonistic competition. The empirical analysis is based on a linked employer-employee data set which allows us to control for heterogeneity both on the worker and on the firm side, and to perform separate analyses for East and West Germany. Our results show important differences in monopsonistic power between industries, and between East and West Germany, which gives an indication of the role of monopsonistic power for inter-industry wage differentials. From a policy point of view, this has important implications for the expected effects of the introduction of a statutory minimum in Germany on 1st Januar 2015.
Keywords: J42; J31; J38; 330